Cold case takedown [large type] - Patch, Jessica R. (Love inspired suspense., 2021)
When cold case podcast host Georgia Maxwell's investigation into her friend's decade-old murder unveils corruption in small-town football, she's thrust into a deadly conspiracy. Her former high school sweetheart and detective, Colt McCoy, steps in to help solve the crime.